An Analysis of the Students’ Perception on Using Live Worksheet for Learning Narrative Text - MAYA RIZKI AMALYASARI; RENA RAHMAWATI; ASTRIANA VIDIA JERINA (Verba: Journal of Applied Linguistics, 2022)
In writing activities in the classroom, there are still many problems found, such as many students are not interested in reading. This is due to the lack of variation in teaching media. Teachers just uses teaching materials that are available in school. The teacher often gives an assignment on the LKS/Lembar Kerja Siswa (students’ worksheet). In this era, technology is very important to us. Through technology, human beings get a lot of information easily and effectively. Liveworksheets is a useful tool for creating interactive exercises for students. It is easy for teachers to use and can make learning more fun and enjoyable. Given the many different options available, however, teachers need to carefully select the most appropriate exercise format required for each learning activity.This study investigated the students' peception on using Live Worksheetfor learning Narrative text at Grade students. This research was a descriptive quantitative study. The data were analyzed through percentage dealing with students’ perception on using Live Workshet for learning Narrative text. According to the result of the questionnaire, it shows that students’ perception on using Live Workshet for learning Narrative text is positive which reached 90,15%. This percentage means that Live Workshet for learning Narrative text is very interesting dan useful for students.